(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: Anemia is a common global health condition characterized by a decrease in the number of red blood cells and inadequate hemoglobin. Iron deficiency anemia and thalassemia are among the leading causes of anemia worldwide. The aim of this study is to investigate red blood cell indices in the coexistence of beta-thalassemia trait (BTT) and iron deficiency anemia (IDA) and evaluate their role in predicting the incidence. Materials and Methods: The study included 110 samples obtained from patients attending the Hematology Department and Central Laboratory at Tishreen University Hospital in Latakia, between April 2021 and June 2022. The final sample was divided into four groups as follow: 33 patients with coexistent thalassemia trait and iron deficiency, 37 patients with beta-thalassemia trait, 20 patients with iron deficiency anemia, and 20 healthy controls. Complete blood counts, hemoglobin separation by HPLC (to assess BTT), serum ferritin measurement (to assess IDA), and patient data collection using a specific form were conducted for the samples. We used specific form to collect the data. Results: The study revealed significant statistical differences between the groups (P-value <0.05) regarding red blood cells parameters and indices. Red blood cell count in patients with coexistente BTT and IDA was within the normal range. The values of Hb, MCV, MCH, and MCHC were decreased, while RDW was increased. The most reliable red blood cell indices in the presence of both diseases were RBC, Hb, and MCV, with threshold values of 6.01 × 1012/L, 11.5 grams/dL, and 75.3 femtoliters respectively. Conclusion: Iron deficiency should be screened in patients with thalassemia trait who have a normal red blood cell count and/or Hb value less than 11.5 grams/dL and/or mean corpuscular volume less than 75.3 femtoliters. The effect of this condition on other red blood cell indices should be assessed.